Analytical Inverse Kinematics-Based Method for a 6-DOF Hexa Parallel Robot - Hendriko Hendriko; Nur Khamdi; Jajang Jaenudin; Roni Novison; Muhammad Ikhsan (Journal of Applied and Computational Mechanics)
This paper presents an analytical inverse kinematic simulation method to define the kinematics aspect of a 6-degree-of-freedom (DOF) Hexa parallel robot. The robot was designed using six independent links, each constructed of upper and lower links. Every link has three joints with a 6-RSS configuration. This configuration is aimed to enhance motion flexibility. In this study, the orientation of the end effector is adjusted based on its position to larger the reach and workspace. The proposed method was implemented to create a computer program in MATLAB, which was used to calculate the motors' motion during a complex path. The results indicate that the developed algorithm can determine the rotation motion of all the motors, which are used to place the end of the arm tool to the target position and orientation. Another verification test was conducted to assess the applicability of the proposed algorithm to a physical robot. The results demonstrated that the proposed approach could perform complex tasks accurately. Moreover, the comparison test proved that the proposed method is more efficient regarding computational time than the Jacobian method. It is the main advantage of the method compared to numerical based method.